1997
DOI: 10.1002/(sici)1097-4644(1997)28/29+<111::aid-jcb12>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐ranging study of Indole‐3‐Carbinol for breast cancer prevention

Abstract: Sixty women at increased risk for breast cancer were enrolled in a placebo-controlled, double-blind dose-ranging chemoprevention study of indole-3-carbinol (I3C). Fifty-seven of these women with a mean age of 47 years (range 22-74) completed the study. Each woman took a placebo capsule or an I3C capsule daily for a total of 4 weeks; none of the women experienced any significant toxicity effects. The urinary estrogen metabolite ratio of 2hydroxyestrone to 16␣-hydroxyestrone, as determined by an ELISA assay, ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 9 publications
2
21
0
4
Order By: Relevance
“…A dose-dependent effect (placebo, 200 and 400 mg/d for 3 months) was observed in the treatment of cervical intraepithelial neoplasia [7] , and 200 or 400 mg/d were similarly effective against vulval intraepithelial neoplasia [14] . In dose-escalation studies for breast cancer prevention, 300 mg/d (minimum) increased the urinary estrogen metabolite ratio of 2-hydroxyestrone to 16 alpha-hydroxyestrone; 800 mg/d did not provide additional benefits over 400 mg/d in adult women [15,16] . Elevated cytochrome P450 activity was responsible for an increase in 2-hydroxylation of estrogen, increasing the ratio of 2-OH:16-OH estrone [16] , which is regarded as favorable for the prevention of breast cancer and human papilloma virus (HPV)-related neoplasias [7][8][9][10][11][12][13][14] .…”
Section: Indole-3-carbinol and Diindolylmethanementioning
confidence: 95%
“…A dose-dependent effect (placebo, 200 and 400 mg/d for 3 months) was observed in the treatment of cervical intraepithelial neoplasia [7] , and 200 or 400 mg/d were similarly effective against vulval intraepithelial neoplasia [14] . In dose-escalation studies for breast cancer prevention, 300 mg/d (minimum) increased the urinary estrogen metabolite ratio of 2-hydroxyestrone to 16 alpha-hydroxyestrone; 800 mg/d did not provide additional benefits over 400 mg/d in adult women [15,16] . Elevated cytochrome P450 activity was responsible for an increase in 2-hydroxylation of estrogen, increasing the ratio of 2-OH:16-OH estrone [16] , which is regarded as favorable for the prevention of breast cancer and human papilloma virus (HPV)-related neoplasias [7][8][9][10][11][12][13][14] .…”
Section: Indole-3-carbinol and Diindolylmethanementioning
confidence: 95%
“…27 A similar six-week study, comparing 0, 50, 100, 200, 300, and 400 mg/day showed that no response was observed at the lower doses, although the responses to 300 and 400 mg were comparable. 28 Cell-culture studies showed that I3C can normalize a pattern of estrogen metabolism in cells treated with DMBA. A similar improvement in the metabolic pattern was also induced by the addition of tamoxifen or HPR to cells treated with DMBA.…”
mentioning
confidence: 99%
“…I3C supplementation has been investigated in 13 published human studies (Table 1) during the past 15 years, totaling 333 study subjects (an estimated 293 subjects on I3C). [25][26][27][28][29][30][31][32][33][34][35][36][37] Since 1991, I3C has been studied for its use in a number of conditions, including patients with human papillomavirus-induced diseases such as cervical cancer 26 and respiratory papillomatosis, [29][30][31] as well as in those subjects with increased risk for breast cancer, 25,36 vulvar intraepithelial neoplasia, 27 and systemic lupus erythematosus. 32 Favorable shifts in estrogen metabolism were observed in studies using these metabolites as clinical end points.…”
Section: Clinical Trial Comparison: Indole-3-carbinol Vs 33-diindolmentioning
confidence: 99%
“…In these studies, 30% to 100% of subjects experienced remission or regression of their symptoms. Two studies explored the use of oral I3C in women with increased risk factors for breast cancer 25,36 : approximately 67 women were studied for 4 weeks to 3 months with an oral I3C dose of 50 to 400 mg. Similar to the studies on human papillomavirus-induced diseases, the results were positive, with a beneficial shift in the ratio of estrogen metabolites.…”
Section: Effect Of Indole-3-carbinol On Estrogen Metabolism Biomarkermentioning
confidence: 99%
See 1 more Smart Citation